(untitled) (Current Horticulture, 2024)
A study was carried out on the morphological and physiological changes in avocado during ripening at ICAR-IIHR, Bengaluru. A promising genotype (IC-0626510) having a large sized green fruits with yield potential of 281 fruits/year was used. Increased weight loss was induced at different stages of ripening from maturity to ripening showing weight loss (11.13% on 8th day) without any change in size of the fruit (9.15 cm x 8.23 cm). At ripening mean pulp recovery >75%, TSS 4.42 °Brix, 38.5%fat, 79.9% moisture, 30g/100g carbohydrate, 4.4% protein and 22.6% fibre was recorded. However firmness of fruits reduced considerably without change in fruit (light green) and pulp colour (creamy-white). There was no incidence of anthracnose on fruits throughout the period of study indicating that fruits of promising genotype are tolerant to anthracnose disease.